The Development of Reading Comprehension and Social Media Literacy According to Akita Action Guidelines for Elementary School - Suthasinee Thanutpitinun (Journal of Educational Issues, 2024)
The research objectives were 1) to study the effectiveness of the skill enhancement form according to the guideline of the Akita action lesson plan on reading comprehension ability and social media literacy; 2) to compare the learning achievement on reading comprehension and social media literacy with the guideline of the Akita action lesson plan before and after learning; 3) to study the satisfaction of students using the guideline of the Akita action lesson plan on reading comprehension and social media literacy; and 4) to study guidelines for solving problems on reading comprehension and social media literacy by implementing the guideline of the Akita action lesson plan. The sampling group consisted of 142 Grade 6 students in Loei Province and interviewed 4 teachers from 4 schools in Loei Province in the second semester of the academic year 2021. The instruments used in this study were the guideline of the lesson plan for developing reading comprehension abilities and social media literacy according to Akita action guidelines, the achievement test, the satisfaction questionnaire, and the semi-structured interview. Learning achievement was compared before and after the study using Paired Sample t-test statistics. The results showed that when teachers applied Akita action guidelines for improving reading abilities and social media literacy. Akita’s action guidelines aroused students to be interested in learning, collaborate in groups to enhance the exchange of knowledge together, and promote the ability to read comprehension and social media literacy. These were consistent with the results of quantitative research, the effectiveness of the skill-enhancing form according to the Akita action guideline plan in terms of reading comprehension and social media literacy, was 81.97/82.32 and 81.06/82.75 respectively, meeting the 80/80 standard. When taking an achievement test, the finding results demonstrated that after they graduated, the scores were significantly higher than before (p < 0.1) and the students’ satisfaction was at a high level.